2023
DOI: 10.3390/buildings13061526
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Electric Arc Furnace Dust (EAFD) on Improving Characteristics of Conventional Concrete

Sajjad Saeb,
José A. Capitán,
Alfonso Cobo

Abstract: The steel industry is one of the key industries and its use is inevitable in many industries including construction. In addition to steel, this industry produces massive amounts of electric arc furnace dust (EAFD) that is classified as hazardous waste. Using this material as an admixture can improve the characteristics of concrete, neutralize potential risks and be beneficial to the circular economy. Considering the differences in EAFD between different steel companies, which in turn is caused by the type and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…And the water absorption of concrete decreased by 9.7%, and for mortar it decreased by 9.3%. This is in good agreement with the works of a number of authors, in particular with the works [13][14][15][16][17][18][19] devoted to the processes of structure formation of concrete composites using coal dust and the works of the authors [20][21][22][23][24][25][26][27] devoted to the physical and mechanical characteristics of concrete modified with coal dust. Based on the results of XRD analysis of concrete of the control composition, the phases of portlandite, illite, anorite, calcite and quartz were identified.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…And the water absorption of concrete decreased by 9.7%, and for mortar it decreased by 9.3%. This is in good agreement with the works of a number of authors, in particular with the works [13][14][15][16][17][18][19] devoted to the processes of structure formation of concrete composites using coal dust and the works of the authors [20][21][22][23][24][25][26][27] devoted to the physical and mechanical characteristics of concrete modified with coal dust. Based on the results of XRD analysis of concrete of the control composition, the phases of portlandite, illite, anorite, calcite and quartz were identified.…”
Section: Resultssupporting
confidence: 90%
“…It should be noted that, based on the results of the literature review, no studies were found on the use of coal dust with a similar chemical composition as a partial replacement for binders in the technology of cement composites. However, there are a number of studies [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] where the use of inert mineral additives, namely, clay, metakaolin, electric arc furnace dust, stone dust and finely ground sea shell powders, as a partial replacement for cement allows in rational amounts the improvement of the physical and mechanical characteristics of the composite and at the same time an increase in its environmental friendliness. The optimal percentages for replacing part of the cement with these types of additives varied from 2% to 20%, while improvements in the strength characteristics, water absorption and porosity of experimental cement composites were observed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations